Partial characterization of β‐ d‐xylosidase from wheat malts. Issue 3 (13th April 2015) - Chai, Yanan; Jin, Yuhong; Du, Jinhua; Li, Jia; Zhang, Kaili
<x xml:space="preserve">Abstract</x> Arabinoxylans (AXs) from wheat malts potentially affect beer quality and production. β‐ d‐Xylosidase is a key enzyme that degrades the main chains of AXs to produce xylose. This study performed a partial characterization of β‐ d‐xylosidase from wheat malts. The optimal temperature was 70 °C and the enzyme exhibited excellent thermostability, that is, residual activities were 92.6% at 60 °C for 1 h. The enzyme was stable over a pH range of 3.0–6.0 and showed optimum activity at pH 3.5 and 4.5. Kinetic parameters Km and Vmax of wheat malt β‐ d‐xylosidase against p‐nitrophenyl‐xyloside were 1.74 mmol L−1 and 0.76 m m min−1, respectively. The enzyme activity was severely inhibited by Cu2+, moderately inhibited by Mn2+, Mg2+, Al3+, Ca2+, Ba2+ and Na+ and mildly inhibited by Fe3+ and Fe2+. The partial enzymatic characterization achieved in this study can be used as a theoretical basis for purifying β‐ d‐xylosidase from wheat malts. Copyright © 2015 The Institute of Brewing & Distilling